2017
DOI: 10.18632/oncotarget.20675
|View full text |Cite
|
Sign up to set email alerts
|

PADI4 rs2240337 G>A polymorphism is associated with susceptibility of esophageal squamous cell carcinoma in a Chinese population

Abstract: BackgroundEsophageal cancer (EC) remains one of the major causes of cancer incidence and mortality worldwide. Genetic factors, such as single nucleotide polymorphisms (SNPs), may contribute to the carcinogenesis of EC.MethodsWe conducted a hospital based case-control study to evaluate the genetic susceptibility of SNPs on the development of EC. A total of 629 esophageal squamous cell carcinoma (ESCC) cases and 686 controls were enrolled for this study. Seven PADI4 SNPs were determined by ligation detection rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…It is an intracellular protein but it had been detected in pIasma samples of the cancer patients as well. In SNPs based study on PADI4, rs2240337 G > A SNP was found to be significantly associated with decreased risk of ESCC 54 . Earlier findings in SNPs study on PADI4 in EC reported rs10437048 and rs41265997 were significantly associated with decreased and increased risk of EC, respectively 53 .…”
Section: Resultsmentioning
confidence: 94%
“…It is an intracellular protein but it had been detected in pIasma samples of the cancer patients as well. In SNPs based study on PADI4, rs2240337 G > A SNP was found to be significantly associated with decreased risk of ESCC 54 . Earlier findings in SNPs study on PADI4 in EC reported rs10437048 and rs41265997 were significantly associated with decreased and increased risk of EC, respectively 53 .…”
Section: Resultsmentioning
confidence: 94%